2016
DOI: 10.1073/pnas.1516812113
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic isoforms of Kaposi sarcoma herpesvirus LANA recruit and antagonize the innate immune DNA sensor cGAS

Abstract: The latency-associated nuclear antigen (LANA) of Kaposi sarcoma herpesvirus (KSHV) is mainly localized and functions in the nucleus of latently infected cells, playing a pivotal role in the replication and maintenance of latent viral episomal DNA. In addition, N-terminally truncated cytoplasmic isoforms of LANA, resulting from internal translation initiation, have been reported, but their function is unknown. Using coimmunoprecipitation and MS, we found the cGMP-AMP synthase (cGAS), an innate immune DNA sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(150 citation statements)
references
References 77 publications
5
140
0
1
Order By: Relevance
“…NOD2-deficient mice had enhanced susceptibility to infection with respiratory syncytial virus (RSV), decreased IRF3 phosphorylation, and type I IFN production. Redundancy of innate immune response pathways to herpesviruses is well known, and some of the recently described pattern recognition receptors, such as IFI16 and cGMP-AMP synthase (cGAS), appear to be broad sensors of different herpesviruses (29,(36)(37)(38)(39)(40)(41). In the case of NOD1, specific HCMV suppression through NOD1 activation (but not HSV-1 suppression) suggests the possible use of specialized pathways through HCMV which could be targeted for virus control.…”
Section: Discussionmentioning
confidence: 99%
“…NOD2-deficient mice had enhanced susceptibility to infection with respiratory syncytial virus (RSV), decreased IRF3 phosphorylation, and type I IFN production. Redundancy of innate immune response pathways to herpesviruses is well known, and some of the recently described pattern recognition receptors, such as IFI16 and cGMP-AMP synthase (cGAS), appear to be broad sensors of different herpesviruses (29,(36)(37)(38)(39)(40)(41). In the case of NOD1, specific HCMV suppression through NOD1 activation (but not HSV-1 suppression) suggests the possible use of specialized pathways through HCMV which could be targeted for virus control.…”
Section: Discussionmentioning
confidence: 99%
“…The latencyassociated nuclear antigen (LANA) is another DNA-binding protein that inhibits IFN-β induction (62) and the transcription of IFN-γ-inducible genes (63). Recently, it was shown that cytoplasmic variants of LANA can inhibit the cGAS-STING DNA-sensing pathway by directly binding to cGAS (47). Interestingly, another KSHV open reading frame, ORF52, was similarly shown to bind and inhibit cGAS enzymatic activity.…”
Section: Latent Kshv Infection and Reactivationmentioning
confidence: 99%
“…Cyclic GMP-AMP (cGAMP) synthase (cGAS) and STING are members of the cytosolic DNA-sensing pathway. This cGAS-STING pathway appears to sense KSHV during both primary infection and reactivation from latency in multiple cell types ( [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have contributed to a body of work that begins to effectively demonstrate the power and function of increased coding capacity in HCMV through transcriptional, translational, and posttranslational mechanisms (9,15,32,33,37,58,59). Further, many examples of viral protein isoforms that have similar or unique functions exist (60)(61)(62)(63)(64)(65)(66)(67), but these examples likely only begin to scratch the surface of the important roles that protein isoforms play in viral infection and virus-host interactions. More work is needed to fully understand the functions of the two pUL138 isoforms and how their functions, in cooperation with the UL133-138 locus, contribute to the persistence of HCMV within the human host.…”
Section: Identified Cd8mentioning
confidence: 99%